2016
DOI: 10.1534/genetics.115.184275
|View full text |Cite
|
Sign up to set email alerts
|

SapTrap, a Toolkit for High-Throughput CRISPR/Cas9 Gene Modification in Caenorhabditis elegans

Abstract: In principle, clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 allows genetic tags to be inserted at any locus. However, throughput is limited by the laborious construction of repair templates and guide RNA constructs and by the identification of modified strains. We have developed a reagent toolkit and plasmid assembly pipeline, called "SapTrap," that streamlines the production of targeting vectors for tag insertion, as well as the selection of modified Caenorhabditis elegans strains. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
191
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(195 citation statements)
references
References 48 publications
3
191
0
1
Order By: Relevance
“…Third, because we generally perform pull-downs using antibodies that recognize protein tags, the assay can be adapted to any protein of interest without re-optimizing conditions. The use of streamlined genome engineering approaches to tag genes (Dickinson et al, 2015; Leonetti et al, 2016; Schwartz and Jorgensen, 2016) facilitates rapid testing of hypotheses using standardized assay conditions. Although we have focused here on cell polarity, our approach should be readily applicable to any cell biological problem that can be modeled in C. elegans embryos, and will be extended to other model systems in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, because we generally perform pull-downs using antibodies that recognize protein tags, the assay can be adapted to any protein of interest without re-optimizing conditions. The use of streamlined genome engineering approaches to tag genes (Dickinson et al, 2015; Leonetti et al, 2016; Schwartz and Jorgensen, 2016) facilitates rapid testing of hypotheses using standardized assay conditions. Although we have focused here on cell polarity, our approach should be readily applicable to any cell biological problem that can be modeled in C. elegans embryos, and will be extended to other model systems in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, to directly study THOC’s function in different neuron types, we utilized a cell-type specific endogenous GFP knock-in strain (Schwartz and Jorgensen, 2016), in which the tagging of the SV protein RAB-3 with GFP was activated by the expression of flippase under different neuron-type specific promoters. We found that cholinergic, GABAergic and serotonergic synapses did not show a dramatic decrease in synaptic density as compared to DA synapses (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…A large pool of mutants, covering majority of the genome, can be directly ordered from C. elegans genetic center (CGC) or the national bioresource project (NBRP). Genome editing by CRISPR-Cas9 technology and conventional transgenic techniques can be readily performed (Mello, Kramer, Stinchcomb, & Ambros, 1991; Schwartz & Jorgensen, 2016). Over 90% of genes can be easily knocked down by bacteria feeding using the RNA interference (RNAi) library (Kamath et al, 2003).…”
Section: Introductionmentioning
confidence: 99%